Introduction Of Innovation in Education in Preschool Organizations (Eurasian Journal of Humanities and Social Sciences, 2021)
On the basis of advanced international experience, introduce modern teaching methods in preschool education and training. They must be innovative, and educational technologies must be creative. A children's preschool organization today is a complex organism striving for improvement, development, looking for new opportunities, creating the necessary conditions to meet the needs of a child, family, society, providing conditions for creative, professional work of teachers, meeting modern requirements. The introduction of innovations into the educational process is not a whim, not an indifferent attitude to the creative search for effective forms of work with children, it is a requirement of the times